IMPLEMENTATION OF FINE ARTS VALUES IN THE WEAVING INDUSTRY AT AGUNG BALI COLLECTION - Sukendy, Thania Aprila; Karja, I Wayan; Tjokropramono, I Gede Yosef (Program Studi Seni Murni ISI Bali, 2025)
This article analyzes the integration of fine art values into the weaving industry at PT. Agung Bali Collection, focuses on the production of creative woven fabric products, such as patchwork paintings. The research identifies technical challenges, such as color consistency and motif complexity, and explores innovative solutions, including modern technology and artisan training. The application of fine art principles like creativity, precision, and cultural significance enhances the aesthetic and cultural value of the products. This study highlights the role of art in preserving cultural heritage while meeting contemporary standards, contributing to the development of the weaving industry.